PROTEIN AND MINERAL PROFILE IN FERMENTED AFRICAN OIL BEAN (PANTACLETHRA MACROPHYLLA BENTH) SEED - C, Egwime E; E, Ossamulu I; O, Akanya H; C, Onuekwusi E; N, Ibeji L (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2018)
The study aimed at evaluating the protein and mineral profile in fermented African oil bean (Pantaclethra macrophylla Benth) seed. Total protein, free amino acid profile, protein fractions, and total mineral content were monitored in the fermenting seed using standard analytical procedures. The total protein content decreased as the fermentation progressed from 45.33 ± 9.24 to 13.30 ± 4.62 mg/100g while free amino acid profile increased from 5.00 ± 3.46 to 22.6 ± 2.31 mg/100g. Glutellin levels increased as the fermentation progressed from 50.6 ± 18.48 to 106.6 ± 4.62 mg/100g while a decrease in levels of albumin, globulin, and prolamin were observed. The mineral and amino acid content was higher than the recommended daily allowance. This study showed that fermented Panthaclethra macropylla Benth seed may be a good source of amino acid and minerals.